answersLogoWhite

0


Best Answer

-4 + 10 + 6a - 2a + 3

9 + 4a

User Avatar

Wiki User

โˆ™ 2017-08-03 13:45:16
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: What is -4 plus 10 plus 6a -2a plus 3?
Write your answer...
Submit
Related questions

What is 2a times 3?

Since the question is 3(2a), then just write it out. 3(2a) is 2a+2a+2a or 6a.


What is 2A times 3 equals 8 plus 4A?

2a*3 = 8+4a 6a = 8+4a 6a-4a = 8 2a = 8 a = 4


What is the answer to 6a-3 equals 8a plus 11?

6a-3=8a+11 -3-11=8a-6a -14=2a a=-7


What is the factor of 6a squared - 17a plus 12?

(2a - 3)(3a - 4)


What is the factor of 6a squared 17a plus 12?

It is: (2a+3)(3a+4) when factored


6a - 5b equals 9 2a plus 5b equals 23?

(4, 3)


How do you factor 2a squared 6a?

I guess you mean: 2a^2+6a Well in this case you take 2a out of the bracket and then you're left with a+3 inside. 2a(a+3a)


If f of x equals 3x - 10 then what is f of 2a?

if f(x) = 3x - 10, then whatever is put (substituted) for x in the "f(x)" bit is substituted for x in the "3x - 10" bit. Thus f(2a) = 3(2a) - 10 = 6a - 10.


What is 2a plus 3b plus 4a?

Think of 2 apples + 3 bananas + 4 apples.What can be added together?6 apples + 3 bananas6a+3b


-8a plus 6a plus 7 equals 1?

-8a + 6a + 7 = 1 -2a = 1 - 7 -2a = -6 a = 6/2 a = 3 Check: -8(3) + 6(3) + 7 = 1 -24 + 18 + 7 = 1 1 = 1


When 3a2-2a plus 5 subtracted by a2 plus a equals 1?

Not sure why it is 3a2- if you mean 3*a*2, then: 3*a*2=6a (6a-2a)+5-2(a (or a2)+a)=1 4a+5-(2a+a)=1 4a+5-2a-a=1 Then take the 5 over (remember, the +5 become -5 when transposed): 4a-2a-a=1-5 Solving the equations on both sides gives: a=-4 Is this your answer?


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-3+5=3b-1


6ab plus 9b divided by 2a plus 3?

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b


a rectangle has a height of a^2+3 and a width of a^2+2a+5. what is the area of the triangle?

Area = [tex]a^4+2a^3+8a^2+6a+15


What is the answer to (2a plus 3)?

It is the expression 3 + 2a.


What is 6A plus A plus 3 simplified?

7A + 3


What is the answer to 3 plus 2a equals?

It is the expression 3 + 2a.


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


What is 5a plus 3 plus 2a-2 plus a?

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1


How many terms in 6a plus 9b plus 15?

There are 3 terms in the given expression of 6a+9b+15


How do you find the sum or difference of (5a2 plus 6a plus 2)-(7a2-7a plus 5)?

Combine like terms, adding/subtracting the coefficients: (5a² + 6a + 2) + (7a² - 7a + 5) = (5+7)a² + (6-7)a + (2+5) = 12a² - a + 7 (5a² + 6a + 2) - (7a² - 7a + 5) = (5a² + 6a + 2) + (-7a² + 7a - 5) = (5-7)a² + (6+7)a + (2-5) = -2a² + 13a - 3


What is 9a plus 8-2a-3-5a?

9a +8 -2a -3 -5a = 2a +5


What is 3a plus 3?

it is 6a


What is 2a plus 3b?

2a + 3b